AB1321 Extra-articular calcifications around the pelvis are highly prevalent and associated with bone mineral density and osteoarthritis. (23rd January 2014) - Sluiter, D.; Kerkhof, H.J.; Hofman, B.; Rivadeneira, F.; Uitterlinden, A.; Bierma-Zeinstra, S.; Oei, E.; van Meurs, J.
Abstract : Background: Extra-articular calcifications are calcified deposits in soft tissue structures outside the joint and are visible on radiographs. Not much is known about the prevalence and aetiology of these extra-articular calcifications, but it is thought that these calcifications develop as a consequence of traumatic events that trigger calcifications of tendons. Objectives: The objective of this study was to determine the prevalence of extra-articular calcifications of the pelvis in an elderly general population and to assess whether these calcifications are associated with hip pain, hip osteoarthritis (OA), osteophytosis and bone mineral density (BMD). Methods: We developed a scoring system for the calcifications, which were scored at five positions around the pelvis: spina iliaca anterior inferior (SIAI), greater trochanter, lesser trochanter, os pubis and tuber ischiadicum. Scores from the calcifications on all 5 locations were added up to make a sumscore variable where a sumscore ≥4 was considered as a case. In 947 subjects, a selection of participants from the Rotterdam Study (a large population-based cohort study of subjects aged ≥55 years), linear regression was used to study the associations between calcifications and lumbar spine (ls) BMD and femoral neck (fn) BMD. To determine the relation between calcifications and hip pain, hip OA and hip osteophytosis, we used a logistic regression model with general estimating equations (GEE). Results: 24% of the subjects had at least one extra-articular calcification around the pelvis. Prevalence was highest at the greater trochanter (12%). We observed that subjects with calcifications had a 7.5% higher ls-BMD ( P =5×10 -5 ) and 4.5% higher fn-BMD ( P =0.01) compared to subjects without a calcification. Calcifications around the greater trochanter were more frequently present in subjects with hip OA (OR 2.04 (95%CI 1.05-3.96), P=0.04) and in subjects with hip osteophytosis (OR 1.50 (95%CI 1.01-2.22), P=0.04). We observed no association between calcifications and hip pain. Conclusions: The prevalence of calcifications around the pelvis is high in an elderly general population. We showed that extra-articular calcifications of the pelvis are related to BMD, hip osteophytosis and hip osteoarthritis. These results might indicate that these extra-articular calcifications are a reflection of bone forming capacity. Disclosure of Interest: None Declared